Matilda - Dahl, Roald; Blake, Quentin (New York, N.Y., U.S.A. Puffin Books, 1990)
Matilda applies her untapped mental powers to rid the school of the evil, child-hating headmistress, Miss Trunchbull, and restore her nice teacher, Miss Honey, to financial security.
The reader of books -- Mr Wormwood, the great car dealer -- The hat and the superglue -- The ghost -- Arithmetic -- The platinum-blond man -- Miss Honey -- The Trunchbull -- The parents -- Throwing the hammer -- Bruce Bogtrotter and the cake -- Lavender -- The weekly test -- The first miracle -- The second miracle -- Miss Honey's cottage -- Miss Honey's story -- The names -- The practice -- The third miracle -- A new home.
Keywords: Schools -- Juvenile fiction; Dysfunctional families -- Juvenile fiction; Girls -- Juvenile fiction; Humorous fiction